A Comparative Study on p- and n-Type Silicon Heterojunction Solar Cells by AFORS-HET - Alkharasani W.; Amin N.; Shahahmadi S.; Alkahtani A.; Bintimohamad I.; Chelvanathan P.; Kiong T. (MDPI, 2023)
Competition; Conversion efficiency; Defects; Electron affinity; Manufacture; Production efficiency; Silicon solar cells; Silicon wafers; AFORS-HET; Crystalline silicon solar cells; Heterojunction solar cells; N type silicon; N- and p-type wafer; P-type silicon; P-type wafer; Rear and front-emitter; Silicon heterojunctions; Simulation; Heterojunctions